Retuning high Q inductive power transfer systems at MHz frequencies: a switched capacitor design method incorporating COSS. Issue 6 (25th March 2023) - Jin, Rui; Gallichan, Robert; Budgett, David; Malpas, Simon; McCormick, Daniel
Abstract: High Q coils are required by inductive power transfer (IPT) links to attain reasonable levels of power transfer especially for loosely coupled links such as those used for small, deeply implanted medical devices. However, the high Q feature makes IPT systems strongly dependent on operating frequency which must be matched in the primary and secondary resonant tanks. Consequently, power transfer is sensitive to resonant frequency shifts due to component aging and environmental factors. Here, a switched capacitor (SC) network is developed to maintain tight matching and enhance system robustness. The combination of high voltage and high frequency required to achieve power transfer to deeply implanted devices makes the SC network design challenging. High frequencies require small tuning capacitance and high voltage requires MOSFETS with large output capacitance ( COSS ) resulting in C OSS having a significant effect on tuning frequency. This paper proposes a parameter design method incorporating C OSS to eliminate the uncertainty of voltage related C OSS . In the experiment, the SC network broadens the effective bandwidth from 37 to 585 kHz at the centre frequency of 6.50 MHz. Across a frequency sweep, the worst case in transfer power drop is −0.43 dB, which demonstrates sufficient immunity to parameter deviations. Abstract : Switched capacitor (SC) network can be applied to inductive power transfer to maintain tight frequency matching and enhance the robustness of power transfer. However, this has not been demonstrated in the MHz frequency range as parasitic capacitance in the MOSFET switching elements is significant when compared to the required tuning capacitance. This paper demonstrates a parameter design method incorporating MOSFET output capacitance (Coss) and experimental results show that the SC network can tune a high Q power transfer link for a deep brain stimulator operating at 6.50MHz.